(untitled) (Gestão & Regionalidade, 2023)
This objective study will understand the dimensions of the context of work, in light of the Psychodynamics of Work, from the perspective of two necrotomists. This is a qualitative study of a descriptive nature, carried out with necrotomists from a Medical-Legal Institute located in Rio Grande do Norte. I used a semi-structured list of questions based on the Work Context Scale (EACT). The strategy used to treat two acquired data was used to analyze the content. Based on the data found, there is no construction of the work context, the social environment where the organization operates, the working conditions and the socio-professional relations, identifying the categories that involve: lack of materials and adequate equipment, unhealthy, division of tarefas, self-management, overload, strictly professional relations, open dialogue and internal conflicts. I hope that this research is constituted as an instrument for reflective discussions and debates about the perception and attribution of meaning to or work for this occupational group.